Interference-free determination of Ca in ultrapure water, concentrated acids and hydrogen peroxide using isotope dilution, ICP-MS and CH3F as a reaction gas - Cardoso Machado, Raquel; Aramendía, Maite; A. Nogueira, Ana Rita; Resano, Martin (Jornada de Jóvenes Investigadores del I3A, 2017)
An analytical method was developed for Ca determination in ultrapure water, concentrated acids and hydrogen peroxide by ICP-MS, using CH3F as reaction gas in the dynamic reaction cell (DRC) and isotopic dilution (ID) as strategy of calibration for improve the accuracy and allow interference- free Ca determination.